APLIKASI MEDIA PEMBELAJARAN ILMU TAJWID DALAM MENGUCAPKAN MAKHARIJUL HURUF HIJAIYAH - Hadi Mulia; Ihda Rahimi; Elma Riska (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
The development of education today can not be separated from the development of science and technology. The education required to always moves with global technological developments. In general, a very important thing to consider in education is the issue of student achievement, particularly in the pronunciation of the letter mahkroj hijaiyah. There are several factors that lead to student achievement such failure. one of which is a lack of will and active participation of students in learning, therefore the author is interested in building a Media Application Tajweed Learning Science in Utter Makharijul Hijaiyah letter. aims to increase the willing and active participation of students in learning the science of recitation. The author has conducted field research, research libraries, and research laboratories. This application will provide a major influence on the attractiveness of the students to learn the science of recitation, especially for students who are more interested in learning visual or audio-visual. And software used was Adobe Flash CS5.